EXAMEN ESPECIAL A LOS RUBROS FONDOS DISPONIBLES Y CARTERA DE CRÉDITO DE LA COOPERATIVA DE AHORRO Y CRÉDITO “HUAQUILLAS”, DEL CANTÓN HUAQUILLAS PROVINCIA DE EL ORO, PERIODO AñO 2013 - Porres Requenes, Erika Tatiana (2015)
This research work called "REVIEW SPECIAL ITEMS AVAILABLE FUNDS AND LOAN PORTFOLIO OF CREDIT union" HUAQUILLAS "HUAQUILLAS CANTON, province of El Oro, PERIOD YEAR 2013" was justified because it generates to the organization value added through the special examination report, where it disclosed the results of the evaluation practiced, becoming a support tool for decision-making and implementation of improvement actions. With the implementation of the Special Examination, giving effect to the main objective of the work proposed and their specific objectives through the three sentences of the special examination as: planning in which knowledge of the cooperative was made, its structure and its main activities, field work which involved in assessing the internal control system by COSO I system, as the most suitable for application to non-governmental entities reviewing the process and verification of available funds and credit portfolio items, determining in turn the level of risk; Additionally specific procedures for each category examined and the findings were applied to meet the relevant evidence and backs of the working papers, explains the third phase is the communication of the results where the opinion on the fairness of the accounts reflected low review of financial statements; if the entity maintained effective internal 5 control structure; if its financial and administrative operations have been performed according to legal, regulatory policy provisions, and other applicable standards.